2018
DOI: 10.3389/fimmu.2018.01928
|View full text |Cite
|
Sign up to set email alerts
|

A Small GTPase, RhoA, Inhibits Bacterial Infection Through Integrin Mediated Phagocytosis in Invertebrates

Abstract: The Ras GTPase superfamily, including more than 100 members, plays a vital role in a number of cellular processes, such as cytoskeleton recombination, gene expression, and signaling pathway regulation. Some members of the superfamily participate in innate immunity in animals. However, there have been few studies of RhoA on this aspect. In the present study, we identified a RhoA GTPase in the shrimp Marsupenaeus japonicus and named it MjRhoA. Expression of MjRhoA was significantly upregulated in hemocytes and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Importantly, small GTPases of the Rab family represent a key cluster of molecules that closely related to phagosome formation and maturation by modulating the remodeling of cytoskeleton. Although no direct evidence about phagosome formation and maturation for engulfing and ingesting microorganism was demonstrated in crustacean, to our best knowledge, several important components, mainly small GTPases members such as Rab6, Rab7, RhoA, and Ran, have been reported in some species of shrimp for their involvement in the signaling cascades of the highly conserved processes (51)(52)(53)(54). Most of them have also been proven previously to play essential roles in regulating the actin polymerization and dynamic remodeling to form phagosome in vertebrates (51).…”
Section: Signaling Cascades Involved In Phagosome Formation and Maturmentioning
confidence: 90%
See 3 more Smart Citations
“…Importantly, small GTPases of the Rab family represent a key cluster of molecules that closely related to phagosome formation and maturation by modulating the remodeling of cytoskeleton. Although no direct evidence about phagosome formation and maturation for engulfing and ingesting microorganism was demonstrated in crustacean, to our best knowledge, several important components, mainly small GTPases members such as Rab6, Rab7, RhoA, and Ran, have been reported in some species of shrimp for their involvement in the signaling cascades of the highly conserved processes (51)(52)(53)(54). Most of them have also been proven previously to play essential roles in regulating the actin polymerization and dynamic remodeling to form phagosome in vertebrates (51).…”
Section: Signaling Cascades Involved In Phagosome Formation and Maturmentioning
confidence: 90%
“…Previously, a C-type lectin receptor, FcLec4, was found to be able to facilitate phagocytosis and bacterial clearance through binding to its receptor βintegrin in F. chinensis (30). Further study showed that MjRhoA participated in hemocytes phagocytosis against V. anguillarum infection via β-integrin-dependent signaling pathway, which was the downstream factor for β-integrin (51). Ran GTPases, another family of the small G protein superfamily, has also been found to be involved in phagosome formation and maturation in crustacean hemocytes.…”
Section: Signaling Cascades Involved In Phagosome Formation and Maturmentioning
confidence: 97%
See 2 more Smart Citations
“…It is known to interact with both Rac2 and Cdc42 to mediate cellular immune responses (Sampson et al, ). The kuruma shrimp, Marsupenaeus japonicas , exhibits cellular immune response to bacterial challenge, in which cytoskeletal rearrangement is mediated by RhoA, a small G protein that is activated by lectin‐integrin signal (Xu et al, ). Rac1 and Rac2 as two members of the Rho GTPase family can regulate cytoskeletal rearrangement and migration of Drosophila hemocytes (Paladi & Tepass, ; Williams, Habayeb, & Hultmark, ).…”
Section: Introductionmentioning
confidence: 99%